2015/16 seasonal vaccine effectiveness against hospitalisation with influenza A(H1N1)pdm09 and B among elderly people in Europe: results from the I-MOVE+ project - Rondy, Marc (2018)
Members of the I-MOVE+ project - Portugal: Baltazar Nunes, Ana Paula Rodrigues, Raquel Guiomar (Infectious Diseases Department, National Health Institute Doutor Ricardo Jorge, Lisbon, Portugal), Victor Gomes, Filipa Quaresma, Luis Vale, Teresa Garcia, Teresa Bernardo, Liliana Dias, Paula Fonseca, Helena Amorim, João Rolo, Helena Pacheco, Paula Branquinho, Rita Côrte-Real (Centro Hospitalar de Lisboa Central, Lisbon, Portugal),José Poças, Paula Lopes, Maria João Peres, Rosa Ribeiro, Paula Duarte, Ermelinda Pedroso, Sara Rodrigues, Ana Rita Silvério, Diana Gomes Pedreira, Marta Ferreira Fonseca, (Centro Hospitalar de Setúbal, Setúbal, Portugal).